Misophonia: Analysis of the neuroanatomic patterns at the basis of psychiatric symptoms and changes of the orthosympathetic/ parasympathetic balance - Grossini, Elena; Stecco, Alessandro; Gramaglia, Carla; De Zanet, Daniel; Cantello, Roberto; Gori, Benedetta; Negroni, Davide; Azzolina, Danila; Ferrante, Daniela; Feggi, Alessandro; Carriero, Alessandro; Zeppegno, Patrizia (Frontiers in Neuroscience, 2022)
Background/Aim Misophonia is a disorder characterized by reduced tolerance to specific sounds or stimuli known as “triggers,” which tend to evoke negative emotional, physiological, and behavioral responses. In this study, we aimed to better characterize participants with misophonia through the evaluation of the response of the autonomic nervous system to “trigger sounds,” a psychometric assessment, and the analysis of the neurological pathways. Materials and methods Participants included 11 adults presenting with misophonic disturbance and 44 sex-matched healthy controls (HCs). Following recently proposed diagnostic criteria, the participants listened to six “trigger sounds” and a “general annoyance” sound (baby crying) during a series of physiological tests. The effects were examined through functional magnetic resonance imaging (fMRI), the analysis of heart rate variability (HRV), and of galvanic skin conductance (GSC). The fMRI was performed on a 3T Scanner. The HRV was obtained through the analysis of electrocardiogram, whereas the GSC was examined through the positioning of silver-chloride electrodes on fingers. Furthermore, the psychometric assessment included questionnaires focused on misophonia, psychopathology, resilience, anger, and motivation. Results Participants with misophonia showed patterns of increased sympathetic activation in response to trigger sounds and a general annoyance sound, the low frequency (LF) component of HRV, the sympathetic index, and the number of significant GSC over the threshold, where the amplitude/phasic response of GSC was higher. The fMRI analysis provided evidence for the activation of the temporal cortex, the limbic area, the ventromedial prefrontal/premotor/cingulate cortex, and the cerebellum in participants with misophonia. In addition, the psychometric assessment seemed to differentiate misophonia as a construct independent from general psychopathology. Conclusion These results suggest the activation of a specific auditory-insula-limbic pathway at the basis of the sympathetic activation observed in participants with misophonia in response to “trigger and general annoyance sounds.” Further studies should disentangle the complex issue of whether misophonia represents a new clinical disorder or a non-pathological condition. These results could help to build diagnostic tests to recognize and better classify this disorder. The relevance of this question goes beyond purely theoretical issues, as in the first case, participants with misophonia should receive a diagnosis and a targeted treatment, while in the second case, they should not.